2023
DOI: 10.1128/spectrum.00770-23
|View full text |Cite
|
Sign up to set email alerts
|

Genomic Diversity of Methicillin-Resistant Staphylococcus aureus CC398 Isolates Collected from Diseased Swine in the German National Resistance Monitoring Program GE RM -Vet from 2007 to 2019

Abstract: The LA-MRSA-CC398 lineage is known for its low host specificity and frequent multiresistance to antimicrobial agents. Colonized swine and their related surroundings represent a considerable risk of LA-MRSA-CC398 colonization or infection for occupationally exposed people through which such isolates might be further disseminated within the human community.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 96 publications
0
1
0
Order By: Relevance
“…Recent reports have identified CC398 as the predominant LA-MRSA clone found in livestock worldwide, including Europe, North America, Asia, and Africa ( Wang et al, 2023 ). LA-MRSA-CC398, lacking specific host specificity, can cross various species barriers, colonize or infect animals and humans through close contact with contaminated livestock or food, leading to human infections ( Tang et al, 2021 ; Kruger-Haker et al, 2023 ). Due to the stable presence of Tn916 and SCCmec in CC398, these mobile genetic elements (or other antibiotic resistance genes) are often retained when CC398 was transmitted to humans ( Matuszewska et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…Recent reports have identified CC398 as the predominant LA-MRSA clone found in livestock worldwide, including Europe, North America, Asia, and Africa ( Wang et al, 2023 ). LA-MRSA-CC398, lacking specific host specificity, can cross various species barriers, colonize or infect animals and humans through close contact with contaminated livestock or food, leading to human infections ( Tang et al, 2021 ; Kruger-Haker et al, 2023 ). Due to the stable presence of Tn916 and SCCmec in CC398, these mobile genetic elements (or other antibiotic resistance genes) are often retained when CC398 was transmitted to humans ( Matuszewska et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, some studies have demonstrated that IEC harbouring LA-MRSA CC398 can be present in animal isolates, and it has also been proposed that LA-MRSA CC398 is capable of re-adapting to the human host (Cuny et al 2015a;Sieber et al 2020;Avberšek et al 2021). However, virulence factors, such as enterotoxin, exotoxin and exfoliative toxin genes, have also been reported, and LA-MRSA CC383 can acquire foreign genetic material by horizontal gene transfer (Krüger-Haker et al 2023). The capability of reobtaining virulence factors and the recent evolution of MRSA CC398 of human origin might pose a greater risk to human and animal health in the future.…”
Section: Evolution Of La-mrsa Cc398 and Other Mrsa Cc398mentioning
confidence: 99%